Electrochemical Performance and Ageing Mechanisms of Sol‐Gel Synthesized Na2/3[Mn3/5Fe2/5]O2 for Sodium‐Ion Batteries. Issue 1 (15th October 2018) - Nayak, Prasant K.; Yang, Liangtao; Pollok, Kilian; Langenhorst, Falko; Wondraczek, Lothar; Adelhelm, Philipp
Abstract: Mn and Fe based layered oxide materials are potential cost‐effective cathodes for application in Na‐ion batteries. In the present study, Na2/3 [Mn3/5 Fe2/5 ]O2 is synthesized by a sol‐gel method using citric acid as chelating agent, followed by annealing at 900 °C for 12 h. The prepared oxide material is characterized by XRD, SEM and TEM. The electrochemical performance of this cathode material is tested through galvanostatic charge‐discharge cycling in the two potential ranges of 2.0–4.2 V and 1.5–4.2 V in Na‐ion half‐cells using Na foil as the counter and reference electrodes. The material exhibits an initial capacity of about 130 mAh g −1 when cycled at 15 mA g −1 in the potential range of 2.0–4.2 V. The capacity decreases to about 105 mAh g −1 upon cycling retaining about 80 % capacity after 100 cycles. When cycled in the potential range of 1.5–4.2 V, a higher initial capacity of about 150 mAh g −1 is found, which decreases to 90 mAh g −1, thus retaining about 60 % capacity after 100 cycles. These results indicate that Na2/3 [Mn3/5 Fe2/5 ]O2 can be a potential cathode material for Na‐ion batteries, when cycled in the potential range of 2.0–4.2 V. TEM analysis of cycled materials shows the formation of secondary Mn−Fe oxide phases along with a change in the oxidation states of the transition metals. The amount of these secondary phases is larger for the sample cycled between 1.5–4.2 V, indicating their crucial role in the ageing mechanism. Abstract : Electrode ageing : sol‐gel synthesized Na2/3 [Mn3/5 Fe2/5 ]O2 is tested as cathode for sodium‐ion batteries and possible aging mechanisms are discussed. TEM/ELNES analysis of cycled materials shows the formation of secondary Mn−Fe oxide phases along with a change in oxidation states of the transition metals. The amount of these secondary phases is larger for the sample cycled between 1.5–4.2 V, indicating the crucial role of the voltage window.